EFFECT OF REAGENT VOLUME AND CONCENTRATION ON RECOVERIES OF MgO AND SO3 WITHIN SYNTHETIC DOLOMITE-BASED KIESERITE - Tatang Wahyudi; Retno Damayanti (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2013)
Natural kieserite is usually used for the production of epsom salt and fertilizer. Normally, the mineral is mined from geologic marine deposits and provides a soluble source of both Mg and S for plant nutrition. However, natural kieserite cannot be found in Indonesia. The fact that this country retains a lot of dolomite deposits and such a material can be processed into synthetic kieserite by sulphatization process seems promising for fertilizer industry in Indonesia. Varying the sulfuric acid concentration between 2 and 5 N and its volume from29.50 to 94.80 ml produces the MgO in MgSO4 filtrate below the specification as stated in Indonesian National Standard (14 – 19%) though its sulfur content has satisfied the requirements. It is assumed that some MgO’s (around 1.93 – 7.12%) are still available in CaSO4 deposit. To get the optimum results, an appropriate calcula- tion is required when adding sulfuric acid to the process and the solution should be in neutral condition prior to separating MgSO4 – CaSO4 as well.